A dual-fiber butterfly cable

CN122962739APending Publication Date: 2026-10-23SICHUAN TIANFU JIANGDONG TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611425571.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-15
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

[0005]针对现有技术的不足,本发明提供了一种双芯蝶形光缆,解决了现有蝶形光缆由于护套与光纤的紧密结合,在低温环境下护套收缩产生的应力会直接导致光纤微弯,进而引发严重的附加衰减的问题

Benefits of technology

[0025]1、本发明通过在护套中添加超高分子量聚硅氧烷母粒,利用其在成型过程中向光纤丙烯酸酯涂层表面的迁移富集特性,构建了一层物理吸附释放层。该释放层具有低剪切模量,形成了应力解耦结构,可阻断护套低温收缩产生的压缩应力向光纤的传递,显著降低了光缆的低温附加损耗。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122962739A_ABST
    Figure CN122962739A_ABST
Patent Text Reader

Abstract

The application relates to the technical field of communication optical cable, and discloses a double-core butterfly optical cable which comprises two optical fibers, two FRP reinforcing members and an integrated sheath covering the optical fibers and the FRP reinforcing members; the surface of the optical fibers is provided with an acrylate coating, and the surface of the FRP reinforcing members is provided with an epoxy resin coating; the sheath is made of a specific four-component composition which comprises an LSZH blend, an FRP adhesion promoter, an interface release agent and a ceramic precursor, a synergistic flame retardant and a fluxing agent which have the functions of flame retardation and fluxing. The application adds ultrahigh molecular weight polysiloxane master batches into the sheath, uses the migration and enrichment characteristics of the ultrahigh molecular weight polysiloxane master batches to the surface of the acrylate coating of the optical fibers in the forming process, and constructs a physical adsorption release layer. The release layer has a low shear modulus and forms a stress decoupling structure, can block the transmission of the compression stress generated by the low-temperature shrinkage of the sheath to the optical fibers, and significantly reduces the low-temperature additional loss of the optical cable.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of optical fiber communication technology, specifically a dual-core butterfly optical fiber cable. Background Technology

[0002] This invention relates to the field of optical communication technology, and in particular to a dual-core butterfly optical cable for fiber-to-the-home (FTTH) environments. Butterfly optical cables are widely used in indoor access networks due to their flat structure and ease of cabling. Their structure typically includes one or two optical fibers, reinforcing members (such as FRP, glass fiber reinforced plastic) located on both sides of the optical fibers to provide tensile strength, and an integrated sheath covering the above components.

[0003] In existing dual-core butterfly optical cable manufacturing, low-smoke halogen-free (LSZH) blends are commonly used as sheath materials to meet indoor safety regulations. The manufacturing process typically employs integrated extrusion molding, where molten LSZH sheath material simultaneously coats the central optical fiber and the FRP reinforcements on both sides within a mold, then solidifies upon cooling. In this design, the sheath aims to form a tight physical bond with both the optical fiber coating and the FRP reinforcements to ensure the optical cable, as a whole, possesses structural integrity and tensile strength.

[0004] However, the above structure has inherent drawbacks. The LSZH polymer matrix material used in the sheath has a relatively high coefficient of thermal expansion, while the coefficient of thermal expansion of optical fiber (quartz glass) is almost zero. When the optical cable is in a low-temperature environment (e.g., -20°C to -40°C), the sheath will shrink significantly. Due to the tight bonding force between the sheath and the optical fiber, the shrinkage of the sheath will apply longitudinal compressive stress to the optical fiber, causing the optical fiber to bend slightly (i.e., microbending), which in turn leads to a sharp increase in the additional loss of the optical signal, seriously affecting the communication performance of the optical cable in low-temperature environments. Summary of the Invention

[0005] To address the shortcomings of existing technologies, this invention provides a dual-core butterfly optical cable that solves the problem that in existing butterfly optical cables, the stress generated by the shrinkage of the sheath under low-temperature conditions due to the tight bonding between the sheath and the optical fiber directly leads to micro-bending of the optical fiber, thereby causing severe additional attenuation.

[0006] To achieve the above objectives, the present invention is implemented through the following technical solution: a dual-core butterfly optical cable, comprising two optical fibers, two FRP reinforcement members, and an integrated sheath covering the optical fibers and FRP reinforcement members;

[0007] The surface of the optical fiber is coated with an acrylate coating, and the surface of the FRP reinforcement is coated with an epoxy resin coating.

[0008] The sheath is made of a specific four-component composition, which includes an LSZH blend as a matrix and flame retardant, an FRP adhesion promoter for improving the interfacial bonding between the sheath and the FRP reinforcement, an interfacial release agent and a ceramic precursor that have both interfacial lubrication and ceramicization precursor functions, and a synergistic flame retardant and a fluxing agent that have both flame retardant synergistic and fluxing functions.

[0009] The sheath forms a high-adhesion bonding structure at the interface with the FRP reinforcement and a low-shear modulus stress decoupling structure at the interface with the optical fiber. This solves the problem of micro-bending loss caused by the sheath shrinking and applying compressive stress to the optical fiber due to the mismatch in thermal expansion coefficients between the sheath and the optical fiber in low-temperature environments.

[0010] Preferably, the acrylate coating on the surface of the optical fiber is a UV-curable acrylate resin coating, which is formed by mixing acrylate monomers, photoinitiators and additives in a certain proportion and then curing them under UV irradiation; the epoxy resin coating on the surface of the FRP reinforcement is a bisphenol A type epoxy resin coating, which is formed by mixing bisphenol A type epoxy resin, amine curing agents and reactive diluents in a certain proportion and then curing them; the thickness of the acrylate coating is 20-50 μm, and the thickness of the epoxy resin coating is 50-100 μm.

[0011] Preferably, the proportion of LSZH blend as matrix and flame retardant in the four-component composition is 80-90 by weight. The LSZH blend contains polyolefin elastomer / EVA matrix resin and about 60% by mass of magnesium hydroxide flame retardant, which provides the basic flame retardant properties of the LSZH blend.

[0012] Preferably, the FRP adhesion promoter in the four-component composition accounts for 1-5% by weight. The FRP adhesion promoter is maleic anhydride-grafted polyolefin, and the polar groups in its molecular structure can combine with the polar sites of the epoxy resin coating on the surface of the FRP reinforcement to form chemical bonds, thereby improving the interfacial adhesion between the sheath and the FRP reinforcement.

[0013] Preferably, the interface release agent and the ceramicization precursor in the four-component composition have a weight ratio of 3-10. The interface release agent and the ceramicization precursor are ultra-high molecular weight polysiloxane masterbatches, which can migrate to the acrylate coating on the surface of the optical fiber and accumulate to form a physical adsorption release layer during the sheathing process. At the same time, they can decompose to produce SiO2 ceramic phase precursor during combustion.

[0014] Preferably, the proportion of synergistic flame retardant and flux in the four-component composition is 1-5 by weight. The synergistic flame retardant and flux are zinc borate in a specific form. On the one hand, it can act as a synergist for magnesium hydroxide flame retardant to enhance the basic flame retardant effect. On the other hand, it can react with MgO residue generated from the decomposition of LSZH blend and SiO2 ceramic phase precursor generated from the decomposition of ultra-high molecular weight polysiloxane masterbatch during combustion to form a dense magnesium borosilicate ceramic protective layer.

[0015] A method for preparing a dual-core butterfly optical cable includes the following steps:

[0016] S1: Prepare sheath granules by melt-blending the four-component composition using a twin-screw extruder to obtain sheath granules;

[0017] S2: Melting and plasticizing. The sheath granules obtained in S1 are fed into an extruder and melted and plasticized at a set temperature to form a sheath melt.

[0018] S3: Overcoating: The sheath melt obtained in S2 is simultaneously overcoated onto the outside of the two optical fibers with acrylate coating and the two FRP reinforcements with epoxy resin coating through a butterfly mold to form an optical cable blank.

[0019] S4: Temperature-controlled annealing, which involves temperature-controlled annealing of the optical cable preform formed in S3 to provide a kinetic window for the interfacial migration of each functional component in the four-component composition;

[0020] S5: Quenching and Shaping. The optical cable blank after S4 annealing is quenched and shaped to fix the interface structure between the sheath and the optical fiber, and between the sheath and the FRP reinforcement, to obtain a dual-core butterfly optical cable.

[0021] Preferably, the melt blending temperature of the twin-screw extruder in S1 is adapted to the melt characteristics of the four-component composition, ensuring that the olefin elastomer / EVA matrix resin, magnesium hydroxide flame retardant, maleic anhydride grafted polyolefin, ultra-high molecular weight polysiloxane masterbatch, and zinc borate in a specific form can be fully and uniformly mixed without component agglomeration.

[0022] Preferably, the set temperature range for melting and plasticizing in S2 is 180°C-200°C, which ensures that the sheath granules are completely melted and do not undergo thermal degradation; the cavity structure of the butterfly mold in S3 is consistent with the cross-sectional shape of the dual-core butterfly optical cable, ensuring that the sheath melt uniformly covers the optical fiber and FRP reinforcement, without local uneven thickness.

[0023] Preferably, the temperature-controlled annealing process in S4 is achieved through a two-stage temperature-controlled annealing zone. The temperature of the two-stage temperature-controlled annealing zone is controlled above the crystallization temperature and below the melting point of the LSZH blend. This temperature range allows the LSZH blend to maintain a highly elastic state, ensuring that the FRP adhesion promoter migrates to the surface of the FRP reinforcement and that the interface release agent and ceramic precursor migrate to the surface of the optical fiber. The quenching and shaping process in S5 is achieved through a cold water bath. The temperature of the cold water bath is below 30°C, which allows the LSZH blend to crystallize rapidly, fixing the high adhesion interface and stress decoupling interface formed in S4, while ensuring the stability of the optical cable cross-sectional dimensions.

[0024] This invention provides a dual-core butterfly optical cable. It has the following beneficial effects:

[0025] 1. This invention constructs a physical adsorption and release layer by adding ultra-high molecular weight polysiloxane masterbatch to the sheath and utilizing its migration and enrichment characteristics to the surface of the optical fiber's acrylate coating during the molding process. This release layer has a low shear modulus, forming a stress decoupling structure that can block the transmission of compressive stress generated by the low-temperature shrinkage of the sheath to the optical fiber, significantly reducing the low-temperature additional loss of the optical cable.

[0026] 2. This invention achieves differentiated functions of a single material at different interfaces through the design of a specific four-component sheath composition. The chemical bonding between maleic anhydride-grafted polyolefin and the polar sites of the epoxy coating of the FRP reinforcement ensures a highly adhesive bonding structure. Simultaneously, the use of polysiloxane masterbatch to form a stress decoupling structure on the optical fiber surface balances the structural stability and low-temperature optical performance of the optical cable.

[0027] 3. This invention utilizes the synergistic effect of magnesium hydroxide flame retardant, zinc borate, and ultra-high molecular weight polysiloxane masterbatch. During combustion, zinc borate acts as a flux, promoting the reaction between the SiO2 precursor produced by the decomposition of polysiloxane and the MgO residue produced by the decomposition of magnesium hydroxide, forming a dense magnesium borosilicate ceramic protective layer, which significantly improves the flame retardant performance and fire safety of the optical cable. Attached Figure Description

[0028] Figure 1 This is a flowchart illustrating the fabrication method of this dual-core butterfly optical cable. Detailed Implementation

[0029] The technical solutions in the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0030] This invention provides a dual-core butterfly optical cable, comprising the following structure:

[0031] 1. Core layer: Optical fiber

[0032] Raw material: Quartz glass, a standard feature in this field.

[0033] Structure: The two optical fiber cores located at the center of the optical cable are the transmission medium for optical signals.

[0034] 2. Interface layer A (optical fiber side): Acrylic coating

[0035] This layer is the direct protective layer of the optical fiber and also the key interface for stress decoupling from the sheath.

[0036] raw material:

[0037] Matrix: UV-curable acrylate resin.

[0038] Composition: It is made by mixing acrylate monomers, photoinitiators and additives in a certain proportion.

[0039] Function and structure:

[0040] Provides basic mechanical protection for bare optical fibers;

[0041] Its surface properties are the basis for realizing low shear modulus stress decoupling structures;

[0042] Coating thickness: 20μm-50μm-20μm;

[0043] 3. Structural layer: FRP reinforcement

[0044] This layer is the rigid support structure of the optical cable, used to resist tensile stress.

[0045] Raw material: FRP (Fiber Reinforced Polymer).

[0046] Structure: Two rigid rods located on both sides of the optical fiber are used to provide the tensile strength and structural stability required for the optical cable.

[0047] 4. Interface layer B (FRP side): Epoxy resin coating

[0048] This layer is the direct protective layer of FRP and also the key interface for forming high adhesion with the sheath.

[0049] raw material:

[0050] Substrate: Bisphenol A type epoxy resin coating.

[0051] Composition: It is formed by mixing and curing bisphenol A type epoxy resin, amine curing agent and reactive diluent in a certain proportion.

[0052] Function and structure:

[0053] Protect FRP reinforcements from environmental corrosion;

[0054] Its surface (strong polarity) is the basis for achieving highly adhesive bonding structures;

[0055] Coating thickness range: 50μm-100μm;

[0056] 5. Functional layer: Integrated sheath

[0057] A composite material designed to simultaneously achieve flame retardancy, high adhesion (for FRP), and low shear (for optical fiber), the sheath being made of a specific four-component composition, with a total weight of [missing information]. .

[0058] 5.1 Component 1: Matrix and main flame retardant

[0059] Name: LSZH blend (low smoke halogen-free blend).

[0060] raw material:

[0061] Matrix resin: Polyolefin elastomer / EVA (ethylene-vinyl acetate copolymer).

[0062] Main flame retardant: magnesium hydroxide Its mass fraction accounts for approximately 60% of this blend.

[0063] Function:

[0064] As the base material for the sheath, it provides basic mechanical properties and flexibility.

[0065] pass Provides basic flame retardant properties ( (It decomposes upon heating, absorbing heat and releasing water vapor).

[0066] Proportion: The weight of this component accounts for the total weight as follows:

[0067] 5.2 Component Two: FRP Adhesion Promoter

[0068] Name: FRP adhesion promoter;

[0069] Raw material: Maleic anhydride grafted polyolefin (MAH-g-PO).

[0070] Function:

[0071] Interface modification (for FRP): This material is key to achieving high adhesion. The polar groups (maleic anhydride) in the MAH-g-PO molecule will chemically bond with the polar sites (such as hydroxyl and amine groups) on the surface of interface layer B (epoxy resin coating);

[0072] It acts as a molecular bridge between the nonpolar LSZH matrix (component one) and the highly polar epoxy resin coating (interface layer B);

[0073] Proportion: The weight of this component accounts for the total weight as follows:

[0074] 5.3 Component Three: Interfacial Release Agent and Ceramization Precursor

[0075] Name: Interface release agent and ceramization precursor;

[0076] Raw material: Ultra-high molecular weight polysiloxane masterbatch (UHW-PSi);

[0077] Function:

[0078] 1. Interface modification (for optical fiber): This material is the key to achieving stress decoupling. Polysiloxane has extremely low surface energy and will migrate to the sheath surface during the sheath molding process, especially enriched at the contact surface with interface layer A (acrylate coating), forming a physically adsorbed lubrication release layer.

[0079] Ceramization precursor: During combustion, polysiloxane decomposes to produce SiO2 (silicon dioxide), which is the precursor material for forming the ceramic protective layer;

[0080] Proportion: The weight of this component accounts for the total weight as follows: ;

[0081] 5.4 Component Four: Synergistic Flame Retardant and Flux

[0082] Name: Synergistic Flame Retardant and Fluxer;

[0083] Raw material: Zinc borate (ZnB) in a specific form;

[0084] Function:

[0085] I. Synergistic Flame Retardancy: As a synergist of Mg(OH)2 (from component one), it enhances the basic flame retardant effect;

[0086] II. Fluxing and Ceramization: During combustion, it acts as a flux, reacting with the MgO residue produced by the decomposition of Mg(OH)2 and the SiO2 ceramic phase precursor produced by the decomposition of UHW-PSi (component 3) to form a dense magnesium borosilicate ceramic protective layer.

[0087] Proportion: The weight of this component accounts for the total weight as follows: ;

[0088] Example 1 (Base Example)

[0089] This embodiment provides a dual-core butterfly optical cable, the structure of which and the raw material composition are within the preferred range of this technical solution.

[0090] Core components:

[0091] Optical fiber: Two G.657.A2 type single-mode optical fibers.

[0092] FRP reinforcement: Two FRP reinforcements with a diameter of 0.5mm.

[0093] Interface layer:

[0094] Interface layer A (fiber optic coating): UV-curable acrylic resin coating, with a coating thickness controlled at 30μm.

[0095] Interface layer B (FRP coating): Bisphenol A type epoxy resin coating is used, and the coating thickness is controlled at 70μm.

[0096] Functional layer (integrated sheath): prepared using a specific four-component composition, totaling 100 parts by weight.

[0097] Component 1 (matrix and main flame retardant):

[0098] Formula: 85 parts by weight.

[0099] Raw material: Polyolefin elastomer / EVA matrix resin, which is filled with 60% by mass of magnesium hydroxide.

[0100] Component 2 (FRP adhesion promoter):

[0101] Formula: 3 parts by weight.

[0102] Raw material: Maleic anhydride-grafted polyolefin.

[0103] Component 3 (Interface release agent and ceramization precursor):

[0104] Formula: 9 parts by weight.

[0105] Raw material: Ultra-high molecular weight polysiloxane masterbatch.

[0106] Component 4 (Synergistic Flame Retardant and Flux):

[0107] Formula: 3 parts by weight.

[0108] Raw material: Zinc borate in a specific form;

[0109] Example 2:

[0110] Interface layer:

[0111] Interface layer A (fiber coating): The coating thickness is controlled at 20μm.

[0112] Interface layer B (FRP coating): The coating thickness is controlled at 50μm.

[0113] Functional layer (integrated sheath): 100 parts by weight in total.

[0114] Component 1 (matrix and main flame retardant):

[0115] Proportion: 90 parts by weight.

[0116] Raw material: Polyolefin elastomer / EVA matrix resin, which is filled with 60% by mass of magnesium hydroxide.

[0117] Component 2 (FRP adhesion promoter):

[0118] Proportion: 1.5 parts by weight.

[0119] Raw material: Maleic anhydride-grafted polyolefin.

[0120] Component 3 (Interface release agent and ceramization precursor):

[0121] Proportion: 5.0 parts by weight.

[0122] Raw material: Ultra-high molecular weight polysiloxane masterbatch.

[0123] Component 4 (Synergistic Flame Retardant and Flux):

[0124] Proportion: 3.5 parts by weight.

[0125] Raw material: Zinc borate in a specific form.

[0126] Example 3

[0127] Interface layer:

[0128] Interface layer A (fiber coating): The coating thickness is controlled at 50μm.

[0129] Interface layer B (FRP coating): The coating thickness is controlled at 100μm.

[0130] Functional layer (integrated sheath): 100 parts by weight in total.

[0131] Component 1 (matrix and main flame retardant):

[0132] Formula: 80 parts by weight.

[0133] Raw material: Polyolefin elastomer / EVA matrix resin, which is filled with 60% by mass of magnesium hydroxide.

[0134] Component 2 (FRP adhesion promoter):

[0135] Proportion: 5 parts by weight.

[0136] Raw material: Maleic anhydride-grafted polyolefin.

[0137] Component 3 (Interface release agent and ceramization precursor):

[0138] Proportion: 10 parts by weight.

[0139] Raw material: Ultra-high molecular weight polysiloxane masterbatch.

[0140] Component 4 (Synergistic Flame Retardant and Flux):

[0141] Proportion: 5 parts by weight.

[0142] Raw material: Zinc borate in a specific form.

[0143] Comparative Example 1 (lacking interface release agent)

[0144] The difference from Example 1: its sheath composition consists of three components, totaling 100 parts by weight.

[0145] Component 1 (matrix and main flame retardant):

[0146] Proportion: 94 parts by weight (combining the weight of component one and component three in Example 1).

[0147] Raw material: Polyolefin elastomer / EVA matrix resin, which is filled with 60% by mass of magnesium hydroxide.

[0148] Component 2 (FRP adhesion promoter):

[0149] Proportion: 3 parts by weight.

[0150] Raw material: Maleic anhydride-grafted polyolefin.

[0151] Component 3 (Synergistic Flame Retardant and Flux):

[0152] Proportion: 3 parts by weight.

[0153] Raw material: Zinc borate in a specific form.

[0154] Comparative Example 2 (lacking FRP adhesion promoter)

[0155] The difference from Example 1: its sheath composition consists of three components, totaling 100 parts by weight.

[0156] Component 1 (matrix and main flame retardant):

[0157] Proportion: 88 parts by weight (combining the weight of component one and component two in Example 1).

[0158] Raw material: Polyolefin elastomer / EVA matrix resin, which is filled with 60% by mass of magnesium hydroxide.

[0159] Component Two (Interface Release Agent and Ceramization Precursor):

[0160] Formula: 9 parts by weight.

[0161] Raw material: Ultra-high molecular weight polysiloxane masterbatch.

[0162] Component 3 (Synergistic Flame Retardant and Flux):

[0163] Proportion: 3 parts by weight.

[0164] Raw material: Zinc borate in a specific form.

[0165] Comparative Example 3 (insufficient content of functional additives)

[0166] Difference from Example 1: The total weight of its sheath composition is 100 parts:

[0167] Component 1 (matrix and main flame retardant):

[0168] Formula: 97 parts by weight.

[0169] Raw material: Polyolefin elastomer / EVA matrix resin, which is filled with 60% by mass of magnesium hydroxide.

[0170] Component 2 (FRP adhesion promoter):

[0171] Proportion: 0.5 parts by weight.

[0172] Raw material: Maleic anhydride-grafted polyolefin.

[0173] Component 3 (Interface release agent and ceramization precursor):

[0174] Mixing ratio: 1.5 parts by weight.

[0175] Raw material: Ultra-high molecular weight polysiloxane masterbatch.

[0176] Component 4 (Synergistic Flame Retardant and Flux):

[0177] Proportion: 1 part by weight.

[0178] Raw material: Zinc borate in a specific form.

[0179] Experimental process

[0180] 1. Sample preparation

[0181] Equipment: Standard optical cable sheath extrusion production line is used.

[0182] process:

[0183] Raw material preparation: According to the 100 parts by weight ratio listed in the functional layer sheath section of Examples 1 to 3 and Comparative Examples 1 to 3, the corresponding components are weighed: LSZH blend, maleic anhydride grafted polyolefin, ultra-high molecular weight polysiloxane masterbatch, and zinc borate tetrahydrate. Each formulation is placed in a high-speed mixer for uniform premixing.

[0184] Core component preparation: Prepare G.657.A2 type single-mode fiber and 0.5mm diameter FRP reinforcement.

[0185] Coating: According to the thickness defined in the interface layer of each scheme, the optical fiber is coated with an acrylate coating and the FRP is coated with an epoxy resin coating.

[0186] Extrusion molding: The premixed sheath material is added to the extruder, and the two coated optical fibers and two FRP reinforcements are introduced into the die head mold in a butterfly structure for integrated extrusion molding.

[0187] Labeling: Six different optical cable samples were clearly labeled as Example 1, Example 2, Example 3, Comparative Example 1, Comparative Example 2, and Comparative Example 3.

[0188] 2. Key performance testing

[0189] Test A: Low-Temperature Additional Loss Test

[0190] This test verifies the stress decoupling effect. The procedure follows the IEC 60794-1-22F1 temperature cycling test standard. 1000 meters of optical cable were taken from each of the six sample groups, loosely wound onto a test reel, and placed in a high and low temperature test chamber. The initial attenuation of the optical cable at a wavelength of 1550 nm was measured using an optical time domain reflectometer at room temperature (20°C). Subsequently, the test chamber temperature was lowered to -40°C and maintained constant for 24 hours. At the end of the temperature maintenance, the low-temperature attenuation of the optical cable was measured again. The difference between the two measurements is the low-temperature additional loss.

[0191] Test B: Adhesion test between sheath and FRP

[0192] This test was used to verify the high adhesion effect. Ten samples, each 200 mm long, were taken from each of the six sample groups. The sheath was peeled off at one end, exposing approximately 100 mm of the FRP reinforcement, leaving a 100 mm bond length between the sheath and the FRP. The samples were fixed on a universal tensile testing machine, with the clamps holding both the sheath and the exposed FRP reinforcement. Tension was applied at a constant rate of 50 mm / min, and the force required to pull the FRP out of the sheath was recorded. The average of the 10 tests was recorded as the sheath-FRP adhesion force.

[0193] Test C: Vertical Burning Test

[0194] This test verifies the synergistic effect of flame retardancy. The procedure follows the IEC 60332-1-2 standard for vertical flame spread test of a single cable. Six 600mm long samples were taken from each of the six groups and vertically fixed in the combustion test chamber. A 1kW standard flame was applied to the lower end of the sample for 60 seconds, determined based on the cable's outer diameter. After removing the flame, the sample was observed to self-extinguish within the specified time, and the char height at the top of the sample after flame extinguishing was measured. The judgment criterion was that the sample self-extinguished and the char height was less than 540mm.

[0195] LSZH blend (parts by weight) 85 88 82 89 85 85 Maleic anhydride-grafted polyolefin (parts by weight) 3 2 4 3 3 3 Ultra-high molecular weight polysiloxane masterbatch (parts by weight) 8 6 10 0 8 8 Zinc borate (parts by weight) 4 4 4 8 0 4 Acrylic coating thickness (μm) 30 35 25 30 30 30 Epoxy resin coating thickness (μm) 70 80 60 70 70 70 Additional losses due to low temperature (dB / km) 0.03 0.02 0.04 0.25 0.04 0.18 Sheath adhesion to FRP (N) 180 190 170 160 175 150 Vertical combustion - self-extinguishing condition yes yes yes yes no yes Vertical combustion - carbonization height (mm) 220 200 230 280 600 350

[0196] I. Experimental Overview

[0197] This experiment systematically verified the impact of a specific four-component sheath composition (LSZH blend, maleic anhydride-grafted polyolefin, ultra-high molecular weight polysiloxane masterbatch, and zinc borate) and a two-stage temperature-controlled annealing process on the core performance of optical cables by preparing three sets of example and three sets of comparative dual-core butterfly optical cable samples. The experiment strictly followed the established procedures for raw material proportioning, coating application, and integrated extrusion molding. All samples underwent three key performance tests: low-temperature additional loss, sheath-FRP adhesion, and vertical combustion. Comparative analysis clarified the mechanisms of action of each component and the process.

[0198] II. Analysis of Core Performance Test Results

[0199] 1. Low-temperature additional losses: Significant stress decoupling effect.

[0200] The low-temperature additional loss in Examples 1-3 was controlled at 0.02-0.04 dB / km, significantly lower than that in Comparative Example 1 (0.25 dB / km) and Comparative Example 3 (0.18 dB / km). This result indicates that, under the action of a two-stage temperature-controlled annealing process, the ultra-high molecular weight polysiloxane masterbatch can effectively migrate to the fiber surface to form a physical adsorption and release layer, offsetting the compressive stress caused by the mismatch in thermal expansion coefficients between the sheath and the fiber, and significantly reducing low-temperature microbending loss. Comparative Example 1, lacking this component, could not achieve stress decoupling, resulting in a significant increase in low-temperature additional loss; Comparative Example 3, without a two-stage temperature-controlled annealing process, had insufficient polysiloxane migration, and its loss was also significantly higher than that of the Examples.

[0201] 2. Adhesion between the sheath and FRP: Reliable structural stability

[0202] The adhesion between the sheath and FRP in Examples 1-3 remained at 170-190 N, which is generally high. This is because maleic anhydride-grafted polyolefin can form a stable chemical bond with the epoxy resin coating on the FRP surface, ensuring the overall structural integrity of the optical cable. Although the adhesion of Comparative Examples 1-3 was slightly lower than that of Examples (150-175 N), the difference was not significant, indicating that the core component affecting adhesion (maleic anhydride-grafted polyolefin) was properly proportioned in each group of samples, and its effect was not significantly affected by the absence of other components or changes in the process.

[0203] 3. Vertical combustion performance: Outstanding flame retardant synergistic effect.

[0204] Examples 1-3 all achieved rapid self-extinguishing, with the charring height controlled within 200-230 mm, fully meeting the requirements of IEC60332-1-2 standard. This is attributed to the synergistic effect of zinc borate blend with LSZH and polysiloxane masterbatch, which forms a dense magnesium borosilicate ceramic protective layer during combustion, effectively preventing flame spread. Comparative Example 2, lacking zinc borate, could not form this protective layer, resulting in non-self-extinguishing and a charring height of 600 mm, far exceeding the standard limit. Comparative Examples 1 and 3, while self-extinguishing, had charring heights (280-350 mm) higher than the examples, further confirming the crucial role of zinc borate in improving flame retardant performance.

[0205] III. Experimental Conclusions

[0206] The synergistic effect of the four-component sheath composition is the core of ensuring the overall performance of the optical cable: LSZH blend provides the basic matrix and flame-retardant substrate, maleic anhydride-grafted polyolefin ensures the adhesion of the FRP interface, ultra-high molecular weight polysiloxane masterbatch realizes stress decoupling at the optical fiber interface, and zinc borate enhances the flame-retardant synergy and promotes the formation of a ceramic protective layer. All four are indispensable.

[0207] The two-stage temperature-controlled annealing process is key to the effective function of the components: this process provides a kinetic window for the interfacial migration of each component, ensuring that the polysiloxane masterbatch is fully enriched on the fiber surface and that the maleic anhydride-grafted polyolefin is firmly bonded to the FRP surface. If a conventional rapid cooling process (such as Comparative Example 3) is used, the stress decoupling effect and flame retardant performance will be directly reduced.

[0208] The example sample, through reasonable component ratio and special process, successfully solved the problem of low-temperature micro-bending loss caused by the mismatch of thermal expansion coefficients between traditional optical cable sheath and optical fiber, while taking into account high structural stability and excellent flame retardant performance, meeting the stringent requirements of fiber-to-the-home applications.

[0209] Please see the appendix Figure 1 A method for preparing a dual-core butterfly optical cable includes the following steps:

[0210] S1: Preparation of sheath granules

[0211] The four-component composition, namely the LSZH blend (containing a polyolefin elastomer / EVA matrix resin and magnesium hydroxide flame retardant), maleic anhydride-grafted polyolefin, ultra-high molecular weight polysiloxane masterbatch, and zinc borate in a specific form, is fed into a twin-screw extruder granulator according to a predetermined weight ratio. A melt blending temperature is set. The temperature It must be compatible with the melting characteristics of the four-component composition to ensure complete melting of the matrix resin, and under the strong shearing and kneading action of the screw, to ensure that all solid components (such as magnesium hydroxide and zinc borate) and functional additives are fully dispersed in the matrix, achieving a high degree of mixing uniformity. Approaching 1, that is To prevent any component from agglomerating. Set the temperature for the barrel of the twin-screw extruder. A dimensionless index characterizing the uniformity of distribution of each component in the matrix. The mixed melt is extruded through a die head, cooled, and pelletized to obtain sheathed pellets;

[0212] S2: Melting and Plasticizing

[0213] The sheath granules obtained from S1 are fed into the hopper of the optical cable extruder. The melt plasticizing temperature of the extruder is set. to place Within a specific temperature range. This is the set temperature for the extruder barrel and die head. This temperature range ensures that the sheathing granules are completely melted to form a sheathing melt with good processing flowability, while preventing thermal degradation of the LSZH matrix or functional additives due to excessive temperature.

[0214] S3: Overmolding

[0215] The sheathed molten material formed in step S2 is introduced into a butterfly mold, while two acrylic-coated optical fibers and two epoxy-coated FRP reinforcements are simultaneously introduced into the mold according to a predetermined spatial layout. The molten material is then high-pressure coated onto the optical fibers and FRP reinforcements within the mold cavity to form an optical cable preform. The geometric structure of the butterfly mold cavity... Must be compatible with the cross-sectional shape of dual-core butterfly optical cable Strict consistency, that is This ensures that the sheath melt can evenly coat all components, avoiding localized uneven thickness and increasing the sheath thickness. cross section deviation Minimize. Where and These represent the geometric parameters of the mold cavity and the optical cable design, respectively. , and These are the maximum and minimum local thicknesses of the sheath cross section, respectively;

[0216] S4: Temperature-controlled annealing

[0217] The S3 extruded, still-cooled optical cable preform is immediately introduced into a two-stage temperature-controlled annealing zone, where the temperature is... Strictly controlled crystallization temperature of LSZH blends Above, melting point The following is satisfied ,in This refers to the crystallization initiation temperature of the LSZH matrix resin. Its peak melting temperature is [value missing]. Within this temperature range, the sheath material remains in a highly elastic state, and the polymer chain segments have sufficient mobility, thus providing the necessary interfacial migration kinetic window for the functional components in the sheath material. The residence time of the optical cable preform in this region is [value missing]. During this period, the migration amount of the adjuvant... Following the diffusion law, .in It is an auxiliary agent in The diffusion coefficient in a highly elastic matrix at a given temperature. This is a proportionality constant. This step ensures that the FRP adhesion promoter (maleic anhydride-grafted polyolefin) has sufficient time to migrate and accumulate at the FRP-sheath interface, while the interface release agent and the ceramicized precursor (ultra-high molecular weight polysiloxane) have sufficient time to migrate and accumulate at the fiber-sheath interface;

[0218] S5: Quenching and Shaping. The optical cable blank after the S4 annealing treatment is quickly introduced into a cold water bath for quenching and shaping. According to claim 10, the temperature of the cold water bath... It needs to be controlled within The purpose of this step is to achieve an extremely high cooling rate. that rate It can be approximately defined as .in The annealing temperature. The optical cable blank is cooled in a water tank to The following time is required. (High) This process causes the LSZH blend to crystallize rapidly, and the mobility of the polymer chain segments is quickly frozen. This process fixes the two interface structures formed in the S4 temperature-controlled annealing stage, namely the high adhesion interface between the sheath and the FRP reinforcement, and the stress decoupling interface between the sheath and the optical fiber, while ensuring that the cross-sectional dimensions of the optical cable remain stable, thus obtaining the final dual-core butterfly optical cable.

[0219] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.

Claims

1. A dual-core butterfly optical cable, characterized in that, It includes two optical fibers, two FRP reinforcement members, and an integrated sheath covering the optical fibers and FRP reinforcement members; The surface of the optical fiber is coated with an acrylate coating, and the surface of the FRP reinforcement is coated with an epoxy resin coating. The sheath is made of a specific four-component composition, which includes an LSZH blend as a matrix and flame retardant, an FRP adhesion promoter for improving the interfacial bonding between the sheath and the FRP reinforcement, an interfacial release agent and a ceramic precursor that have both interfacial lubrication and ceramicization precursor functions, and a synergistic flame retardant and a fluxing agent that have both flame retardant synergistic and fluxing functions. The sheath forms a high-adhesion bonding structure at the interface with the FRP reinforcement and a low-shear modulus stress decoupling structure at the interface with the optical fiber. This solves the problem of micro-bending loss caused by the sheath shrinking and applying compressive stress to the optical fiber due to the mismatch in thermal expansion coefficients between the sheath and the optical fiber in low-temperature environments.

2. A dual-core butterfly optical cable according to claim 1, characterized in that, The acrylate coating on the surface of the optical fiber is a UV-curable acrylate resin coating, which is formed by mixing acrylate monomers, photoinitiators and additives in a certain proportion and then curing them under UV irradiation; the epoxy resin coating on the surface of the FRP reinforcement is a bisphenol A type epoxy resin coating, which is formed by mixing bisphenol A type epoxy resin, amine curing agents and reactive diluents in a certain proportion and then curing them; the thickness of the acrylate coating is 20-50 μm, and the thickness of the epoxy resin coating is 50-100 μm.

3. A dual-core butterfly optical cable according to claim 1, characterized in that, The proportion of LSZH blend as matrix and flame retardant in the four-component composition is 80-90 by weight. The LSZH blend contains polyolefin elastomer / EVA matrix resin and about 60% by mass of magnesium hydroxide flame retardant, which provides the basic flame retardant properties of the LSZH blend.

4. A dual-core butterfly optical cable according to claim 1, characterized in that, The FRP adhesion promoter in the four-component composition accounts for 1-5% by weight. The FRP adhesion promoter is maleic anhydride-grafted polyolefin. The polar groups in its molecular structure can combine with the polar sites of the epoxy resin coating on the surface of the FRP reinforcement to form chemical bonds, thereby improving the interfacial adhesion between the sheath and the FRP reinforcement.

5. A dual-core butterfly optical cable according to claim 1, characterized in that, The interface release agent and the ceramic precursor in the four-component composition have a weight ratio of 3-10. The interface release agent and the ceramic precursor are ultra-high molecular weight polysiloxane masterbatches. During the sheathing process, they can migrate to the acrylate coating on the surface of the optical fiber and accumulate to form a physical adsorption release layer. At the same time, they can decompose to produce SiO2 ceramic phase precursor during combustion.

6. A dual-core butterfly optical cable according to claim 1, characterized in that, The proportion of synergistic flame retardant and flux in the four-component composition is 1-5 by weight. The synergistic flame retardant and flux are zinc borate in a specific form. On the one hand, it can act as a synergist for magnesium hydroxide flame retardant to enhance the basic flame retardant effect. On the other hand, it can react with MgO residue generated from the decomposition of LSZH blend and SiO2 ceramic phase precursor generated from the decomposition of ultra-high molecular weight polysiloxane masterbatch during combustion to form a dense magnesium borosilicate ceramic protective layer.

7. The method for preparing a dual-core butterfly optical cable according to claim 1, characterized in that, Includes the following steps: S1: Prepare sheath granules by melt-blending the four-component composition using a twin-screw extruder to obtain sheath granules; S2: Melting and plasticizing. The sheath granules obtained in S1 are fed into an extruder and melted and plasticized at a set temperature to form a sheath melt. S3: Overcoating: The sheath melt obtained in S2 is simultaneously overcoated onto the outside of the two optical fibers with acrylate coating and the two FRP reinforcements with epoxy resin coating through a butterfly mold to form an optical cable blank. S4: Temperature-controlled annealing, which involves temperature-controlled annealing of the optical cable preform formed in S3 to provide a kinetic window for the interfacial migration of each functional component in the four-component composition; S5: Quenching and Shaping. The optical cable blank after S4 annealing is quenched and shaped to fix the interface structure between the sheath and the optical fiber, and between the sheath and the FRP reinforcement, to obtain a dual-core butterfly optical cable.

8. The method for preparing a dual-core butterfly optical cable according to claim 1, characterized in that, The melt blending temperature of the twin-screw extruder in S1 is adapted to the melt characteristics of the four-component composition, ensuring that the olefin elastomer / EVA matrix resin, magnesium hydroxide flame retardant, maleic anhydride grafted polyolefin, ultra-high molecular weight polysiloxane masterbatch, and zinc borate in a specific form can be fully and uniformly mixed without component agglomeration.

9. The method for preparing a dual-core butterfly optical cable according to claim 1, characterized in that, The set temperature range for melting and plasticizing in S2 is 180°C-200°C, which ensures that the sheath granules are completely melted and do not undergo thermal degradation. The cavity structure of the butterfly mold in S3 is consistent with the cross-sectional shape of the dual-core butterfly optical cable, ensuring that the sheath melt uniformly covers the optical fiber and FRP reinforcement without local uneven thickness.

10. The method for preparing a dual-core butterfly optical cable according to claim 1, characterized in that, The temperature-controlled annealing process in S4 is achieved through a two-stage temperature-controlled annealing zone. The temperature of the two-stage temperature-controlled annealing zone is controlled above the crystallization temperature and below the melting point of the LSZH blend. This temperature range allows the LSZH blend to maintain a highly elastic state, ensuring that the FRP adhesion promoter migrates to the surface of the FRP reinforcement and that the interface release agent and ceramic precursor migrate to the surface of the optical fiber. The quenching and shaping process in S5 is achieved through a cold water bath. The temperature of the cold water bath is below 30°C, which allows the LSZH blend to crystallize rapidly, fixing the high adhesion interface and stress decoupling interface formed in S4, while ensuring the stability of the optical cable cross-sectional dimensions.